Irish Industrial Exposition, World's Fair, St. Louis, U.S.A.
Buildings listed: Irish National Theatre, Cormac's Chapel, Blarney Castle, Industrial Hall, Ross Castle, McKinley's Cottage, St. Lawrence Gate, Irish Houses of Parliament.